Coeliccia mientrung spec. nov. from Central Vietnam (Odonata: Platycnemididae) - Kompier, Tom; Phan, Quoc Toan (Zootaxa, 2017)
Coeliccia mientrung spec. nov. is described from central Vietnam. Detailed differences from the very similar C. pyriformis Laidlaw, 1932, are provided. The female of C. pyriformis is described for the first time.